Effects of Forest Harvesting Operations on Suspended Sediment and Solute Loads in the Sungai Weng Experimental Watersheds, Kedah, Peninsular Malaysia - Akkharath, Inthavy (2005)
This study examines the effects of logging operations on sediment and solute yields in four steep catchments referred to as the Sungai Weng Experimental Watersheds located in Ulu Muda Forest Reserves Kedah, Peninsular Malaysia. Watershed 1 (W 1) is a control catchment where logging was not allowed throughout the period of study. Watershed 2 (W2) was logged based on stringent guidelines as recommended by the Forestry Department hitherto referred to as reduced impact logging (RIL). Watershed 3 (W3) was logged based on conventional logging (CL) practices. Watershed 5 (W5) is a bigger watershed, where the experimental basins are nested within and selected to examine the downstream and cumulative effects of logging operations including in those areas worked previously. The general aim of this study was to compare the relative impacts of CL and RIL on sediment output. In this study, the extent of sediment source areas in W2 and W3 in the form of roads, skid trails and log landings and their implication on sediment output was also examined. In W2, the logging roads density was 30 mlha, while the density of skid trail was 68 mlha and the exposed area was 43 ha, about 5% of total watershed area. In W3, the logging road density was 47 rnlha and the density of skid trail was 10lmha; exposed area was 59 ha, about 9% of watershed area. The most reliable and suitable method was chosen to determine the sediment yield of the four catchments was estimated using data assembled for the rising and falling discharge stages. In W 1, suspended sediment concentrations are high during storms even though under natural forests. The peak concentrations sampled were between 1,278 to 1,896 mgll from 1997 to 2002 respectively. The annual sediment yields were 160, 199, 148, 97, 79, and 80 t/km2/yr generated fiom 1997 to 2002 respectively. During logging operations, in W2, the annual sediment yields significantly increased from 176 to 1,15 1 t/km21yr in year 2000 and 2002 respectively. In W3, the sediment yields increased dramatically to 2,133; 5,386; 4,501 t/km2/yr over the period of 1998 to 2000 respectively. After logging ceased, sediment yield decreased to 869 and 684 t/km2/yr from 2001 and 2002 respectively. Sediment yield in W5 was much less even though, the sediment yields fiom the experimental watersheds W3, in particular was high. Depositions of sediment along the stream channel leading to the gauging . . . 111 site of W5 and dilution from upstream channels were the main reason for the lower yield. Therefore, in W5 the sediment yield was contributing 143, 284, 829,458, 178, and 163 tlkm2/yr, in over the six-year period from 1997 to 2002 respectively. Stream water quality was measured in each study watershed and the results revealed that solute loads were much lower than sediment loads. In W1, the annual solute yields were 12.5, 13.5, 20.1, 14.8, 13.7, and 13.8 tlkm2/yr generated from 1997 to 2002 respectively. During logging operations, in W2, solute yields were 20.3, 13.4, 11.3 t h 2 / y r , for the year 2000, 2001 and 2002, respectively. In W3, solute out put was 30.8, 27.0 and 20.0 t/lun21yr. However, the annual sediment yields appeared to have declined to 18.0 and 14.2 tkm2/yr, in the following two years 2001 and 2002, respectively. In W5, solute out put was contributing 17.5, 16.8, 27.0, 25.4, 23.1 and 17.3 tlkm2/yr, in over the six-year period from 1997 to 2002. The results of the study suggest that with proper control measures, the effects of logging on sediment loads in particular, can be substantially reduced. The increase of sediment yield in W2 to l,l5 1 t/km21yr in 2002 with 80% the study watershed was logged suggests that RIL exerted significant influence on sediment output. With respect to pre-logging or control conditions, the analyses suggest that conventional logging can results in over 40 times the sediment yield during the logging operations. The positive effects of RIL can be achieved through carehl planning, scheduling and control of logging operations.